Response of plasmodesmata formation in leaves of C4 grasses to growth irradiance - Danila, Florence R.; Quick, William Paul; White, Rosemary G.; von Caemmerer, Susanne; Furbank, Robert T. (Wiley, 2019)
Rapid metabolite diffusion across the mesophyll (M) and bundle sheath (BS) cell interface in C4 leaves is a key requirement for C4 photosynthesis and occurs via plasmodesmata (PD). Here, we investigated how growth irradiance affects PD density between M and BS cells and between M cells in two C4 species using our PD quantification method, which combines three‐dimensional laser confocal fluorescence microscopy and scanning electron microscopy. The response of leaf anatomy and physiology of NADP‐ME species, Setaria viridis and Zea mays to growth under different irradiances, low light (100 μmol m−2 s−1), and high light (1,000 μmol m−2 s−1), was observed both at seedling and established growth stages. We found that the effect of growth irradiance on C4 leaf PD density depended on plant age and species. The high light treatment resulted in two to four‐fold greater PD density per unit leaf area than at low light, due to greater area of PD clusters and greater PD size in high light plants. These results along with our finding that the effect of light on M‐BS PD density was not tightly linked to photosynthetic capacity suggest a complex mechanism underlying the dynamic response of C4 leaf PD formation to growth irradiance.